Affectivity and Philosophy after Spinoza and Nietzsche Making Knowledge the Most Powerful Affect - Pethick, Stuart; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
Pethick investigates a much neglected philosophical connection between two of the most controversial figures in the history of philosophy: Spinoza and Nietzsche. By examining the crucial role that affectivity plays in their philosophies, this book claims that the two philosophers share the common goal of making knowledge the most powerful affect.
Keywords: Philosophy; Ethics; Modern philosophy; Language and languages -- Philosophy; Philosophy; History of Philosophy; Philosophy of Language; Ethics; Modern Philosophy; Electronic books